Disease‐associated polymorphisms in 9p21 are not associated with extreme longevity. Issue 6 (26th September 2014) - Congrains, Ada; Kamide, Kei; Hirose, Nobuyoshi; Arai, Yasumichi; Oguro, Ryousuke; Nakama, Chikako; Imaizumi, Yuki; Kawai, Tatsuo; Kusunoki, Hiroshi; Yamamoto, Hiroko; Onishi‐Takeya, Miyuki; Takeya, Yasushi; et al.
<x xml:space="preserve">Abstract</x> Aim The 9p21 region has been pointed out by the genome‐wide association studies as a hot spot for disease‐associated variants. Most of the diseases linked with the locus are aging‐related conditions, such us cardiovascular disease, diabetes and cancer. Centenarians are known to present a reduced risk and delayed onset for these conditions. Here, we aimed to assess if the 9p21 variants contribute to this protection by possibly altering basic aging mechanisms. Methods We genotyped 15 tag single‐nucleotide polymorphisms (SNP) along the CDKN2A/B/ANRIL locus in 1505 individuals. The participants were divided in three groups: centenarians, septuagenarians and young controls. Centenarians were 593 participants (age range 100–116 years, mean 105.9 years), septuagenarians were 434 volunteers aged between 69 and 71 years (mean 70.1 ± 0.9 years) and the 478 young controls were under the age of 50 years (range 14–50 years, mean 41.8 years). We genotyped the SNP rs1333049 in an additional sample of 231 coronary artery disease patients to confirm the 9p21 association. Results The leading coronary artery disease‐associated SNP rs1333049 was associated with coronary artery disease; however, none of the 9p21 SNP evaluated in the present study were associated with extreme longevity. Conclusions Our findings suggest that the 9p21 disease‐associated polymorphisms do not contribute to the life‐long protection from cardiovascular and other age‐related diseases observed in centenarians. It is likely that this protection is mediated by mechanisms different from the ones underlying the 9p21 association. Geriatr Gerontol Int 2015; 15: 797–803.